The effectiveness of the clinical nurse leader practice - systematic review - Carvalho, Marlene Celeste; Lucas, Pedro Ricardo (Millenium - Journal of Education, Technologies, and Health, 2020)
Introduction: The leadership of clinical nurse leaders is a topic of increasing importance, since nurses, as leaders, are the fundamental piece to communicate with the team and achieve objectives and results, such as the quality of nursing care, the patient safety and health innovation. Objectives: To analyze the scientific evidence about the effectiveness of nurses in the development of skills associated with the practice of clinical leader. Methods: Systematic literature review with 3 steps. 1) An initial search at CINHAL and MEDLINE. 2) A broader search, using the same keywords and search terms, in the remaining databases of the EBSCO Host platform. 3) Search the bibliographic references of the selected articles. The selected studies were from the period between 2010 and 2019. Results: Twelve articles were selected in different contexts of clinical nurse leader practice. Most reported findings that relate the effectiveness of clinical nurse leaders with clear improvements in performance and, consequently, improvement in health care outcomes. Conclusions: The skills of the clinical nurse leader are part of an advanced practice, with better performances that lead to an increase in the quality of nursing care, health care and an increase in patient safety.